Notes on infinity : a novel - Taylor, Austin, 1999- (Celadon Books, 2025)
"A singular, extraordinary debut about Zoe and Jack, Harvard students who find themselves propelled into the intoxicating biotech startup world when they announce they've discovered the cure for aging. A different kind of love story where the thirst for achievement consumes and the stakes are forever. Zoe, the daughter of an MIT professor who grew up in her brother's shadow, can envision her future anew at Harvard. Jack, a boy in Zoe's organic chemistry class with unruly hair and a gleam of competitiveness, matches her intellect and curiosity with every breath. When Jack refers Zoe for a position in a prestigious professor's lab, the two become entwined as colleagues, staying up late to discuss scientific ideas. They find themselves on the cusp of a breakthrough: the promise of immortality through a novel antiaging drug. Zoe and Jack set off on their new project in secret. Finding encouraging results, they bring their work to an investor, drop out of Harvard, and form a startup. But after the money, the magazine covers, and the national news stories detailing their success, Zoe and Jack receive a startling accusation that threatens to destroy both the company they built and their partnership. A captivating novel about young love, the allure of immortality, and the recklessness that can come with early success, Notes on Infinity asks: How far would you go to achieve your dreams?"--